A Statistical Comparison of Employee Education Attainment to Customer Service Oriented Governmental Organization Employee Performance - Rudolph, Christopher C., Jr (ProQuest LLC, 2023)
Quantitative research on education and training attainment involving wage data using "Human Capital" theoretical constructs provides insights based on monetary returns. However, similarly determining quantifiable values for the education and training attainment of individual governmental organization employees relative to their respective work performance has proven an elusive prospect. Given that individual employee performance at governmental organizations is not directly tied to marketplace success, this research endeavor explored establishing a non-monetary value linking an individual's education and training attainment to their work performance as service providers. This undertaking used service user survey comment card response data in an attempt to compare governmental organization employee higher education and training attainment levels. Herein, it was hypothesized that archival survey data could be used to determine the effect higher education and training have on the service user survey satisfaction scores applicable to individual government workers. It was further hypothesized that the higher a governmental organization employee's educational and training attainment, the greater the level of user satisfaction will be recorded for the service provided. Based on the results of this study, no significance was associated with the subject governmental employees' higher education and training attainment attributes to applicable service user satisfaction scores. However, these results do not preclude future research endeavors in this area of study. Moreover, it is acknowledged that future statistical research in this area may be better served by the evolution of technological advancements in government queuing processes, including the latest implementation of advanced survey research designs. Finally, it is recognized the information gleaned from this research venture serves to benefit governmental organizations, their employees, higher educational institutions, other entities, and the public about the potential predicated by this line of inquiry. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]